Genetic diversity and structure of Callosobruchus maculatus populations in the different agro-ecological zones of Senegal - Faye, Aliou; Faye, Ablaye; Diome, Toffene; Sembene, Mbacke (Journal of Asian Scientific Research, 2023)
The objective of this study is to determine the diversity and genetic structure of cowpea weevil populations in the different agro-ecological zones of Senegal. Thus, to achieve this objective, individuals of Callosobruchus maculatus from localities in each zone were used, after sampling and massive breeding. The sequenced gene is Cyt-B. The results showed high haplotypic diversity (0.901 ±0.00033) and low nucleotide diversity (0.010 ±0.0000003). These diversities studied by agro-ecological zone show that the Casamance zone has the greatest haplotypic diversity (0.901; P>0.05) while the eastern Senegal zone has the lowest value (0.439; P>0.05). The nucleotide diversity is lower in the Sylvo-pastoral zone (0.00112; P<0.05) and higher in the Casamance zone (0.01052; P<0.05). The genetic structuring shows that the Senegal River Valley-eastern Senegal zone couple is more differentiated [FST(Fixation index)]=0.70687; P<0.05) and the Casamance-Groundnut Basin zone couple is less differentiated (FST=0.21248; P<0.05). The greatest genetic distance was found between the Sylvo-pastoral zone and the River Valley and the smallest between the eastern Senegal zone and the River Valley. However, a significant genetic variation within the populations was noted (64.93%). Overall we have a low level of diversity and weakly structured populations except those of Tamba and Fouta. A slight influence of the zones was also noted.